Parallel and vector computing : - Leiss, Ernst L. (Chapman & Hall/CRC, 1995)
This a practical look at parallel and vector techniques written especially for engineers working in the field. This hands-on guide focuses on the brass-tacks implementation issues they face every day--including those involving programming and input/output. It also suggests solutions to a host of real-world problems.